Effects of Externalities and Flow on Perceived Usefulness, Satisfaction, and Loyalty in Mobile Instant Messaging Promotion - Gloria, Theresa Victory; Achyar, Adrian (ASEAN Marketing Journal, 2021)
At its introduction, instant messaging (IM) was predicted to facilitate communication between businesses and customers. Growing numbers of smartphones coupled with internet penetration then led to the development of mobile instant messaging (MIM). Some MIM provides a feature for businesses to communicate to customers, which enables businesses to send promotions and information directly to customers. For this to be effective, loyalty is crucial for continued MIM use, especially MIM that can be used as a promotional tool, or mobile instant messaging promotion (MIMP). This study focuses on the factors that affect loyalty and satisfaction in MIMP. The results suggest that loyalty is affected by satisfaction and perceived usefulness, satisfaction by perceived enjoyment and attention focus, and perceived usefulness by referent network size and attention focus. MIMP should increase the user referent network size by offering rewards for inviting contacts. Perceived enjoyment and attention focus can be strengthened by enhancing the user experience and offering additional features.